Ultrasound‐Induced Mechanical Compaction in Acoustically Responsive Scaffolds Promotes Spatiotemporally Modulated Signaling in Triple Negative Breast Cancer. Issue 10 (17th February 2022) - Humphries, Brock A.; Aliabouzar, Mitra; Quesada, Carole; Bevoor, Avinash; Ho, Kenneth K. Y.; Farfel, Alex; Buschhaus, Johanna M.; Rajendran, Shrila; Fabiilli, Mario L.; Luker, Gary D.
Abstract: Cancer cells continually sense and respond to mechanical cues from the extracellular matrix (ECM). Interaction with the ECM can alter intracellular signaling cascades, leading to changes in processes that promote cancer cell growth, migration, and survival. The present study used a recently developed composite hydrogel composed of a fibrin matrix and phase‐shift emulsion, termed an acoustically responsive scaffold (ARS), to investigate effects of local mechanical properties on breast cancer cell signaling. Treatment of ARSs with focused ultrasound drives acoustic droplet vaporization (ADV) in a spatiotemporally controlled manner, inducing local compaction and stiffening of the fibrin matrix adjacent to the matrix–bubble interface. Combining ARSs and live single cell imaging of triple‐negative breast cancer cells, it is discovered that both basal and growth‐factor stimulated activities of protein kinase B (also known as Akt) and extracellular signal‐regulated kinase (ERK), two major kinases driving cancer progression, negatively correlate with increasing distance from the ADV‐induced bubble both in vitro and in a mouse model. Together, these data demonstrate that local changes in ECM compaction regulate Akt and ERK signaling in breast cancer and support further applications of the novel ARS technology to analyze spatial and temporal effects of ECM mechanics on cell signaling and cancer biology. Abstract : The study uses a smart hydrogel system with focused ultrasound for precise temporal and spatial control of tissue compaction. Incorporating breast cancer cells into this hydrogel system reveals that ultrasound‐triggered increases in compaction of extracellular matrix promotes signaling through pathways known to drive proliferation and aggressive features in breast cancer and other malignancies.